THE IMPLEMENTATION OF RISK MANAGEMENT IN SOLID WASTE MANAGEMENT (SWM) TO ENHANCE THE QUALITY OF LIFE (A CASE STUDY OF AAP) - John Mathiang Machar Mathiang; Chaerul D. Djakman (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
Effective solid waste management (SWM) is crucial for maintaining environmental sustainability and enhancing the quality of life in communities. However, improper waste management practices pose significant risks to public health, the environment, and social well-being. This study discusses implementing risk management strategies in SWM, focusing on the case of PT. Arta Asia Putra.org is a waste management initiative in a densely populated Malang, East Java urban area. By analysing the organisation’s risk assessment, mitigation measures, and community engagement, this research sheds light on the significance of integrating risk management principles to ensure a safer and healthier living environment. The results show that, while the company does try to effectively manage the risks inherent in its operations by providing safety kits and health insurance for employees working at the dumpsites, several significant challenges persist. These challenges include the absence of established risk management standards within the company, employee non-compliance with safety measures, and the lower educational levels of the workforce. These factors collectively hinder the company's ability to mitigate the risks associated with its operations entirely. To solve the said challenges, the study suggests that there should be comprehensive risk management standards, regular employee training awareness, and incentives for compliance to encourage employees to comply with safety measures